The difficult PICC insertion is associated with the significant increase of complications in 1 month follow-up - Lisova, Katerina; Pavelkova, Katerina; Matejckova, Tereza; Simkova, Petra; Hloch, Ondrej; Charvat, Jiri (The journal of vascular access, 2025)
BACKGROUND: PICC is routinely inserted with assistance of ultrasonography and/or ECG navigation (RI- routine insertion). Only in a minority of patients the insertion of a PICC is difficult and fluoroscopic visualization with introduction of special guidewire is necessary for the success of the procedure (DI-difficult insertion). The aim of the study was to evaluate whether DI can be predicted and associated with a risk of complications during follow-up. METHODS: The study included patients who had a PICC insertion in 2022. The number of patients with RI and DI was recorded and the significance of selected parameters during insertion and the frequency of complications during 1 month follow-up was compared. RESULTS: About 1404 patients had successful PICC insertion in 2022, RI in 1360 (96.8%) and DI in 44 patients (3.2%). There was no significant effect of age, gender, selected vein, its size, insertion site, and tunneling on the course of PICC insertion. However the number of punctures for needle insertion was higher in DI. The complication rate during 1 month follow-up in DI was 9 (20.4%) versus 101 patients (7.4%) in RI (p = 0.002). CONCLUSION: PICC insertion was successful in both RI and DI patients. Of the analyzed parameters, the number of needle punctures was associated with DI, and complications during the 1-month follow-up were more frequently noted in the DI group.
Keywords: dospělí; Punctures; hodnocení rizik; Female; Renal Dialysis; Catheterization, Peripheral; dialýza ledvin; Adult; výsledek terapie; ženské pohlaví; Time Factors; časové faktory; lidé; ultrasonography; ECG navigation; Treatment Outcome; Aged, 80 and over; zaváděcí katétry; Risk Assessment; intervenční ultrasonografie; Risk Factors; Ultrasonography, Interventional; Catheters, Indwelling; retrospektivní studie; PICC; Male; Aged; fluoroscopy; periferní katetrizace; rizikové faktory; Catheterization, Central Venous; katetrizace centrálních vén; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; punkce; complications; Retrospective Studies; Central Venous Catheters; Middle Aged; centrální žilní katétry; Humans